Progress of time-varying gravity in seismic research - Yiqing Zhu; Yong Zhang; Xiong Yang; Fang Liu; Guoqing Zhang; Yunfeng Zhao; Shouchun Wei; Jinglun Mao; Song Zhang (地球与行星物理论评, 2022)
This article mainly introduces the application and progress of ground time-varying gravity in the seismic research of mainland China, and briefly introduces the application of satellite gravity in seismic research. Since the Xingtai earthquake in 1966, China has begun relative gravity monitoring, trying to explore the relationship between gravity changes and seismic activities. The gravity changes before and after the Haicheng MS7.3 earthquake in 1975 and the Tangshan MS7.8 earthquake in 1976 were observed. In 1981, a high-precision Lacoste-Romberg (G) metal spring gravimeter was introduced to conduct the Sino-US cooperative research on earthquake gravity and the practice of high-precision relative gravity observation in the key earthquake monitoring areas in 1984, which was dominated by the earthquake prediction experiment site in western Yunnan. The gravity anomaly changes near the epicenters of the China-Myanmar border MS7.3 earthquakes in 1995 and the Lijiang MS7.0 earthquakes in 1996 were observed. In 1998, introduced high-precision absolute gravity surveys were used to monitor the overall scale gravity field variation in mainland China. Those monitoring obtained the gravity changes before the 2008 Wenchuan MS8.0 and Yutian MS7.3 earthquakes, and proposed adequate opinions for medium-term earthquake prediction. After the Wenchuan MS8.0 earthquake in 2008, the integration of the national network and the regional network formed the whole gravity observation network in China, which made a relatively successful medium-term prediction for a series of earthquakes with MS6.0 or above (such as Lushan MS7.0, Menyuan MS6.4, Hutubi MS6.2, Yutian MS7.3, Jiuzhaigou MS7.0, etc.). The integrated network played an important role in studying earthquake mechanisms and the improvement of medium-term earthquake prediction levels in China. Finally, the existing problems in time-varying gravity monitoring in China are pointed out in this paper, and the prospect of earthquake research by using time-varying gravity monitoring data is put forward.